Some Approximation Properties of q-Baskakov-Beta-Stancu Type Operators. (16th December 2013) - Mishra, Vishnu Narayan; Khatri, Kejal; Narayan Mishra, Lakshmi
Abstract : This paper deals with new typeq -Baskakov-Beta-Stancu operators defined in the paper. First, we have used the properties ofq -integral to establish the moments of these operators. We also obtain some approximation properties and asymptotic formulae for these operators. In the end we have also presented better error estimations for theq -operators.